FUNDESCO: FUNDACIÓN NACIONAL DE SOLIDARIDAD CONTRA EL CANCER DE MAMA - Castro, Marlene (1994)
Devalutlon implications of breast loss, stereotyped symbol of women, make difficult the physic, psychological and and social rehabilitation of the operated. First results of observation: about dlsadvantageous situation of women-patlent facing health institution and the role of FUNDESCO ln the solution to thls problem, are presented ln thls article